Implementasi Asset Based Community Development: Strategi Peran Pemimpin dalam Pemberdayaan Masyarakat berbasis Circular Economic pada Unit Usaha Syariah - Kurniawan, Fakhry Hafiyyan; Santoso, Budi; Sobandi, Ade; Maulana, Mahbub Afini; Fitrina, Gina Dwi (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
Youth have an important role in society, one of the organizations in society that houses youth is Karang Taruna. Along with the growth of business units operating in the fisheries sector, there are several environmental problems. The aim of the research is how to develop a community empowerment strategy based on circular economics. The research method used is qualitative with ABCD & SWOT analysis, the sample is the Sukabumi City Farmer Youth Business Group. The research results show that community groups have implemented the ABCD program, and it can be said that there are several empowerment strategies in business sustainability namely motivation, conducting training, making wise decisions, managing resources optimally, and building marketing networks.